Current-driven phase-change optical gate switch using indium–tin-oxide heater. (26th June 2017) - Kato, Kentaro; Kuwahara, Masashi; Kawashima, Hitoshi; Tsuruoka, Tohru; Tsuda, Hiroyuki
Abstract: We proposed and fabricated a current-driven phase-change optical gate switch using a Ge2 Sb2 Te5 (GST225) thin film, an indium–tin-oxide (ITO) heater, and a Si waveguide. Microfabrication technology compatible with CMOS fabrication was used for the fabrication of the Si waveguide. The repetitive phase changing of GST225 was obtained by injecting a current pulse into the ITO heater beneath the GST225 thin film. The switching operation was observed by injecting a 100-ns current pulse of 20 mA into the ITO heater. The average extinction ratio over the wavelength range of 1, 525 to 1, 625 nm was 1.2 dB.